Molecular structure controlled self-assembly of pyridine appended fluorophores: multi-stimuli fluorescence responses and fabricating rewritable/self-erasable fluorescent platforms. Issue 3 (14th January 2021) - Gayathri, Parthasarathy; Pannipara, Mehboobali; Al-Sehemi, Abdullah G.; Moon, Dohyun; Anthony, Savarimuthu Philip
Abstract : Pyridine appended structural isomers showed a planar or propeller conformation dependent molecular self-assembly, fluorescent polymorphs, stimuli-responsive fluorescence switching and halochromism. Abstract : The fluorescence properties of organic materials are intrinsically governed by the molecular conformation and intermolecular interaction mediated aggregation. Herein, we have synthesized two sets of isomeric fluorescence molecules with a partially planar and propeller structure, ( Z )-3-(4-(9 H -carbazol-9-yl)phenyl)-2-(pyridinyl)acrylonitrile (1–3 ) and ( Z )-3-(4-(diphenylamino)phenyl)-2-(pyridinyl)acrylonitrile (4–6 ) and explored their effect on the molecular aggregation, and tunable and switchable solid state fluorescence. Molecular aggregation studies revealed the formation of 1D nanostructures of nanoparticles with the evolution of intermolecular interactions with increasing water fraction and time. The evolution of nanostructures led to a tunable fluorescence from green to red. The subtle structural change and formation of different crystal forms/polymorphs resulted in a tunable fluorescence between 514 and 644 nm ( Φ f = 11.3 to 25.3%). Solid state structural studies showed relatively weak intermolecular interactions in the crystal lattice of 1, 3 and 6 that resulted in the formation of different crystal forms/polymorphs and varied molecular assemblies with tunable fluorescence. Mechanofluorochromism (MFC) studies also showed molecular structure dependent fluorescence switching. 1–3 and 6 showed crushing/heating induced reversible fluorescence switching whereas 4 and 5 did not show any MFC. Integrating an acid/base sensitive pyridine functionality has been exploited for demonstrating halochromic reversible fluorescence switching as well as fabricating rewritable/self-erasable fluorescent platforms on filter paper and glass plates.